APPLICATION OF THE LEVELS OF INQUIRY METHOD IN INCREASING STUDENT ACHIEVEMENT IN IPBA MATERIALS - Wijaya, Hari Rachmat (PT. Antis International Publisher, 2025)
Objective: This research is motivated by the low learning achievement of students in IPBA materials, especially in the cognitive domains of knowing, applying, and reasoning. This is based on the results of the TIMSS (Trends in International Mathematics and Science Study) survey in 2011, 2015, and 2019. Based on the results of observations, the ability to know, apply, and reason are abilities that are less facilitated in the IPBA learning process in the classroom. One of the learning alternatives that is seen as having ways that can train knowing, applying, and reasoning skills is learning with levels of inquiry (LOI). Therefore, the study aims to determine the contribution of the application of LOI in improving student learning achievement in the domains of knowing, applying, and reasoning. Method: The research design used in the study was a one group pretest-posttest design with a research sample of 35 students at one of the State Junior High Schools in Pandeglang Regency. Results: Based on data analysis using effect size, it was found that the effect size value of 0.75 in the knowing domain and 0.71 in the reasoning domain was in the medium category. Meanwhile, the effect size value of 1.32 in the applying domain is in the large category. This shows that the implementation of the LOI makes a moderate contribution to the improvement of the domain of knowing and reasoning. However, the LOI makes a significant contribution to the improvement of domain applying. Novelty: This research highlights the targeted use of Levels of Inquiry (LOI) to specifically enhance the cognitive domains of knowing, applying, and reasoning—domains often under-supported in IPBA learning—providing empirical evidence of its differentiated impact across cognitive dimensions.